Pelatihan Dan Sosialisasi “Aplikasi Smart Imunisasi (ASI)” Untuk Deteksi Stunting Anak Usia Dini Menuju Indonesia Bebas Stunting - Paradise Paradise; Muhammad Afrizal Amrustian; Maliana Puspa Arum (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Sawangan Village, which is one of the villages in Kebasen District, Banyumas Regency, is one of the villages that focuses on reducing stunting rates. According to the interviews we conducted with Posyandu cadres, they experienced problems during the weighing and measuring process. So far, Posyandu cadres have had trouble in the process of weighing and measuring the height of toddlers, because the process is still using conventional tools. In the process of recording the growth and development of children under five is done by recording using a boloin in a book. Because the recording was done by hand, it was constrained by handwriting which was difficult to read. Based on these problems, Forum Group Discussion (FGD) activities were carried out, socialization and training on the use of digital scales, outreach and training on the use of the website-based “Smart Immunization Application” system and Android mobile. The number of participants in this activity was 17 people. Indicators of the success of the activities that have been carried out are coordination with partners, management of a team of lecturers as assistant partners, training on the use of digital scales, training and outreach systems. Based on the activities that have been carried out, it can be concluded that this activity is of interest to Posyandu cadres and parents of toddlers as evidenced by the enthusiasm of the participants. Obstacles faced are not all parents use smartphones, internet access, and constraints on parents' age.